PENGARUH PROFESIONALISME AUDITOR INTERNAL TERHADAP PENCEGAHAN DAN PENDETEKSIAN KECURANGAN (FRAUD) - Widaningsih, Mimin; Nur Hakim, Desy (Jurnal Riset Akuntansi dan Keuangan, 2015)
This study aims to determine the effect of internal auditor professionalism on the prevention and detection of fraud (fraud) on SOEs with headquarters in Bandung. The research method used in this research is descriptive method associative. The data used are primary data collected through the spread of questionnaires on Nine SOEs with Head Office in Bandung. This study uses non-parametric statistical test with Spearman Rank with SPSS 20.0 for Windows software.The results showed that the influence of professionalism of internal auditor to fraud prevention is 40.07%, and the rest of 59.93% can be influenced by other variables that are not examined. And the amount of influence of professionalism of internal auditors to the detection of fraud is 37.33%, the rest of 62.67% can be influenced by other variables that are not examined.